TVET Teaching Strategy during COVID-19: A Comparative Study of Indonesia and Malaysia - Ana, A -; Halim, Fazlinda Binti Ab; Barliana, Mokhamad Syaom; Ilhamdaniah, Ilhamdaniah; Mulyadi, Yadi; Salira, Ade Budhi; Muktiarni, Muktiarni; Sari, Ana Ramdani; Muda, Wan Hanim Nadrah Binti Wan (Journal of Technical Education and Training, 2021)
The purpose of this study is to gain an understanding of the teaching strategies used by lecturers in Indonesia and Malaysia during the COVID-19 pandemic. Many lecturers must consider the amount of teaching they can provide. The transition from offline to online learning, which is accompanied by extensive technological use, is extremely challenging. A survey study was designed using an online questionnaire. The questionnaire is including items on learning objectives, lesson materials, teaching and learning activities, learning design, media, resources, and learning evaluations. A Google Form-based online questionnaire is used to collect the data. The research participants are TVET lecturers from two universities in Indonesia and Malaysia with 200 valid responses. Descriptive statistics such as frequency distribution, mean, and standard deviation are used to analyse the research data. Inferential statistics, t-test is used to investigate the difference between two countries, Malaysia and Indonesia on the teaching strategies during the pandemic. The results show that Indonesian and Malaysian lecturers have similar preferences for lesson material, learning resources, teaching and learning activities. While learning objectives, learning design, media, and learning evaluation are all distinct and interconnected. Most Malaysian lecturers agree that online learning allows for greater teaching flexibility, more caring, and is more open to meet the needs of students. Other than that, the t-test show no difference in teaching strategies between Malaysia and Indonesia. For the conclusion, lecturers at both universities adapt quickly to the changes that occur during each phase of the pandemic. The most effective teaching strategies are presented to ensure that educational services and processes continue to perform.